Peripheral Nerve Stimulation Enters the Mainstream: A New Era for Long-Term, Non-Pharmacologic Pain Management - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
Chronic pain affects over 150 million individuals across Europe and the United States, posing a major public health challenge due to its complexity, persistence, and limited treatment success. This report briefly outlines a recent study presenting the largest real-world registry to date on micro-implantable peripheral nerve stimulation (PNS), including over 2,200 patients with chronic peripheral neuralgia or neuropathy. In this study 94% of patients reported clinically meaningful improvements which highlights the broad applicability, consistency, and durability of micro-IPG PNS in clinical management of chronic pain. Compared to conventional non-pharmacologic modalities such as CBT, physical therapy, acupuncture, and TENS, implantable PNS offers deeper, more targeted neuromodulation without reliance on patient adherence or exposure to systemic side effects. While challenges such as surgical implantation, patient selection, and cost remain, PNS stands poised to become a front-line, precision-based therapy for chronic neuropathic pain. To realize its full potential, broader access through primary care integration, provider training, digital support tools, and reimbursement reform is essential. As healthcare shifts away from opioids, PNS offers a transformative option to address chronic pain with long-term efficacy, safety, and scalability.
Keywords: Chronic pain; Peripheral nerve stimulation; Micro-implantable device; Neuropathic pain; Non-pharmacologic therapy